DEVELOPMENT OF ULTRA-HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR THE DETERMINATION OF CAPTOPRIL IN PHARMACEUTICAL DOSAGE FORMS - Logoyda, Liliya; Kondratova, Yuliya; Korobko, Dmytro; Soroka, Yuriy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of this research was to develop more simple, sensitive, accurate, and less expensive analytical methods for the determination of captopril in medicines by Ultra-high-performance liquid chromatography. Materials and Methods: The chromatographic analysis of captopril performed on liquid chromatography Agilent 1290 Infinity II LC System. Results: A simple, rapid, sensitive, and specific method was developed for the determination of captopril by ultra-high-performance liquid chromatography in mono-medicines and pharmaceutical dosage forms in combination with hydrochlorothiazide without previous separation. Satisfactory resolution was achieved using Fused-CoreÂ® technology Ascentis Express C18 column (4.6Ã—150 mm) and a mobile phase consisting of methanol and 0.1% solution of trifluoroacetic acid (40/60, v/v) at a flow rate 1.2 mL/minute and the wavelength detection was 220 nm. Ascentis Express columns, based on FusÐµd-core pÐ°rticle technÐ¾logy, prÐ¾vide more than twice the speed and efficiency of traditiÐ¾nal cÐ¾lumns at half the backpressure of sub-2-Î¼m columns. The retention time for captopril was 1.345 minute. The validation of this method was based on the ICH and USP guidelines. Conclusion: The results obtained in this research work clearly indicated that the assay was rapid, sensitive and successfully applied to the determination of both drugs in pharmaceutical dosage forms without interference from tablet excipients.